EMPIRICAL MODELS FORLOSSES CALCULATION IN A RECTANGULAR DUCT EQUIPPED BYARTIFICIALROUGHNESS - CHOUCHANE, N.; MOUMMI, A.; BRIMA, A.; MOUMMI, N. (Courrier du Savoir; Vol. 13 (2012): Courrier du Savoir, 2014)
The objective of this work is to find empirical models linking load losses to the geometric characteristics of artificial roughness called baffles and different modes of provisions of these fluids in the vein of a rectangular channel. An experimental design was set up to measure the lossesLoadcausedby baffles between the upstream and downstream of the channel. The experimental measurements made have enabled us to establish empirical relationships to evaluate losses in accordance with load losses configuration and arrangement of baffles and for different flow regimes.